Strategi Bertahan Hidup Petani Kopi Pasca Konflik (Studi Kasus di Kecamatan Kute Panang Kabupaten Aceh Tengah) - Suryadi Suryadi; Ahmad Humam Hamid; Agussabti Agussabti (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2013)
ABSTRACT. This study aims to know the survival strategies used by coffee farmers in post- conflict Kute Panang district of Central Aceh and what factors are dominant over coffee growers survival strategies in post-conflict Kute Panang district of Central Aceh. This study is using a qualitative approach through phenomenological observation of the 24 villages in the districts in Central Aceh. Techniques of data collection by observation, in-depth interviews and literature study. The findings of the field for a survival strategy adopted, among others, Productions Strategy, Patronage Strategy, Vertical Solidarity Strategi, Strategy Owe, Accumulation Strategy, Strategy Odd, Manipulation Strategies Commodities, Temporary Migration Strategy, while the dominant factors of the survival strategy of internal factors such as an awareness of crop production is seasonal, lack of employment, low amounts of revenues and expenses to need, to be influenced by external factors family support, support neighbors